Pengaruh Strategi Menyanyi dan Gaya Belajar Audiotori Terhadap Penguasaan Kosa kata Bahasa Arab Siswa MI Thoriqul Huda Wagir - Maghfiroh; Munirul Abidin (Education Research Center, 2025)
This study aims to analyze the effect of singing strategy and audiotory learning style on the mastery of Arabic vocabulary of Madrasah Ibtidaiyah Thoriqul Huda Wagir Malang students. The background of this study is based on the importance of learning approaches that are in accordance with the characteristics of students' learning styles in an effort to improve foreign language competence early on. This study used a quantitative approach with multiple linear regression method. The sample consisted of 41 students, who were selected through purposive sampling technique. The research instruments were a closed questionnaire and an Arabic vocabulary mastery test. The results of the analysis show that simultaneously, the singing strategy and audiotory learning style have a significant effect on the mastery of Arabic vocabulary, as indicated by a significance value of 0.000 and R square of 0.600. However, partially, only the audiotory learning style has a significant effect (p = 0.000), while the singing strategy does not show a significant effect (p = 0.838). This shows that audiotory learning style is the dominant factor in supporting the mastery of Arabic vocabulary in madrasah students.Based on this finding, it is recommended that Arabic teachers integrate learning strategies that support students' audiotory learning styles, such as the use of audio media, singing, and verbal repetition.